Rifaximin in non‐alcoholic steatohepatitis: An open‐label pilot study. Issue 1 (31st May 2017) - Cobbold, Jeremy F.L.; Atkinson, Stephen; Marchesi, Julian R.; Smith, Ann; Wai, Sann N.; Stove, Julie; Shojaee‐Moradie, Fariba; Jackson, Nicola; Umpleby, A. Margot; Fitzpatrick, Julie; Thomas, E. Louise; Bell, Jimmy D.; et al.
Abstract : Aim: Gut microbial dysbiosis is implicated in the pathogenesis of non‐alcoholic steatohepatitis (NASH). We investigated downstream effects of gut microbiota modulation on markers of hepatic inflammation, steatosis, and hepatic and peripheral insulin sensitivity in patients with NASH using rifaximin therapy. Methods: Patients with biopsy‐proven NASH and elevated aminotransferase values were included in this open‐label pilot study, all receiving 6 weeks rifaximin 400 mg twice daily, followed by a 6‐week observation period. The primary endpoint was change in alanine aminotransferase (ALT) after 6 weeks of rifaximin. Secondary endpoints were change in hepatic lipid content and insulin sensitivity measured with a hyperinsulinemic–euglycemic clamp. Results: Fifteen patients (13 men and 2 women) with a median (range) age of 46 (32–63) years were included. Seven had diabetes on oral hypoglycemic medications and 8 had no diabetes. After 6 weeks of therapy, no differences were seen in ALT (55 [33–191] vs. 63 [41–218] IU/L, P = 0.41), peripheral glucose uptake (28.9 [19.4–48.3] to 25.5 [17.7–47.9] μmol/kg/min, P = 0.30), hepatic insulin sensitivity (35.2 [15.3–51.7]% vs. 30.0 [10.8–50.5]%, P = 0.47), or hepatic lipid content (21.6 [2.2–46.2]% vs. 24.8 [1.7–59.3]%, P = 0.59) before and after rifaximin treatment. After 12 weeks from baseline, serum ALT increased to 83 (30–217) IU/L, P = 0.02. There was a significant increase in the homeostasis model assessment–estimated insulin resistance index ( P = 0.05). The urinary metabolic profile indicated a significant reduction in urinary hippurate with treatment, which reverted to baseline after cessation of rifaximin, although there was no consistent difference in relative abundance of fecal microbiota with treatment. Conclusion: These data do not indicate a beneficial effect of rifaximin in patients with NASH.